Analisis Hasil Audit Atas Pelaporan Dana Kampanye Partai Politik P Di Kabupaten Q - Rindy Maylita Hapsari; Hero Priono (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research focuses on the Analysis of Audit Results on the Campaign Fund Reporting of Political Party P in District Q. The objective of this study is to identify and analyze the compliance of Political Party P with the campaign fund reporting regulations set by the General Elections Commission (KPU), specifically PKPU No. 18 of 2023, as well as to evaluate the strengths and weaknesses in the party's financial reporting system. This study employs a qualitative method approach using secondary data. Data collection methods include interviews with party officials and auditors, as well as documentation. The results of this study indicate that Political Party P in District Q has not fully complied with PKPU No. 18 of 2023, thus categorizing Party P as a Non-Compliant Party. The non-compliance in campaign fund reporting has led to a decrease in transparency and accountability of Party P and a decline in public trust in the party.